(untitled) (Journal Of Educational and Psychological Researches, 2025)
The research aims to identify the effect of the Cosgrove model on generative thinking among fourth-year scientific students in physics by verifying the following hypothesis: "There is no statistically significant difference at the level of (0.05) between the average grades of the female students of the experimental group who studied according to the Coscrov model and the average grades of the female students of the control group who studied according to the traditional method of generative thinking." The researchers used an experimental design with partial control through the post-test. The research population is determined by female students in the fourth scientific grade of government secondary and preparatory schools for girls in the center of Baghdad Governorate (Al-Karkh III) for the academic year (2023-2024). The research sample consisted of 60 students: 30 female students for the experimental group and 30 female students for the control group. The researcher conducted a statistical equivalence of the two groups in terms of chronological age, previous achievement, mental abilities test, and generative thinking test. A generative thinking test consisting of 31 items was developed by the researchers. The results revealed that the experimental group outperformed the control group in the generative thinking test. In light of the research results, the researchers presented several recommendations and suggestions.